The clinical value of circulating free tumor DNA in testicular germ cell tumor patients - Boublikova, Ludmila; Kramarzova, Karolina Skvarova; Zwyrtkova, Martina; Bakardjieva-Mihaylova, Violeta; Stuchly, Jan; Rosova, Blanka; Kolostova, Katarina; Sonsky, Jindrich; Kindlova, Eva; Zachoval, Roman; Buchler, Tomas; Trka, Jan (Urologic oncology, 2022)
BACKGROUND: Testicular germ cell tumors (TGCT) are unique malignancies of young adult men; their biology is, however, underexplored and there has not been much progress in their treatment for decades. Circulating free tumor DNA (cfDNA) analysis represents a promising way of discovering novel diagnostic and treatment options. OBJECTIVE: The study evaluates the clinical value of cfDNA detection in TGCT patients. DESIGN AND METHODS: Total cfDNA concentration and ratio of its 2 main fragments (180 and 360 bp) were evaluated by spectrophotometry, capillary electrophoresis and qPCR in peripheral blood plasma of 96 TGCT patients (173 samples) and 31 normal controls. Non-parametric tests were used for statistical analyses. RESULTS: The total cfDNA concentration was significantly higher in TGCT than in controls (P < 0.0001), with the highest levels at disease progression, but with no clear threshold between malignant and normal samples. Patients with positive tumor markers had higher cfDNA concentrations than those with negative markers (P = 0.01). Longer 360 bp cfDNA fragments were found in 58% of TGCT patients including almost all samples from relapse or disease progression but no normal controls (P < 0.0001). CONCLUSION: Total cfDNA levels are significantly increased in TGCT patients but without a clear threshold separating normal and tumor samples, thus total cfDNA amount itself is not a sensitive enough marker to identify or monitor TGCT. Longer cfDNA fragments have been found exclusively in a proportion of tumors and predominantly at disease progression, representing a novel potential marker for TGCT monitoring that would deserve further exploration.
Keywords: Cell-Free Nucleic Acids; Circulating Tumor DNA; cirkulující nádorová DNA; Biomarkers, Tumor; Humans; lidé; Neoplasms, Germ Cell and Embryonal; mužské pohlaví; Male; progrese nemoci; nádorové biomarkery; volné cirkulující nukleové kyseliny; Testicular Neoplasms; Disease Progression; Young Adult; mladý dospělý; germinální a embryonální nádory; testikulární nádory